Characterization of Febrile Neutropenia in Pediatric Patients With Cancer Before and After Implementation of Coronavirus Disease 2019 Precautions. Issue 4 (20th May 2023) - Kibby, Danielle; Trinkman, Heidi; Ray, Anish; Hamby, Tyler; Orr, Kaci
Abstract : Historically, febrile neutropenia (FN) has constituted a common but life-threatening emergency in pediatric oncology patients. As such, hygiene precautions have consistently been recommended for immunosuppressed patients. These precautions, however, were more strictly and widely adopted during the coronavirus disease 2019 pandemic. Universal mask mandates, emphasis on hand hygiene, and encouragement of social distancing were some of the many initiatives introduced in an effort to reduce transmission of the virus. There is little data available regarding whether the universal adoption of these precautions was associated with any changes in the incidence of hospitalizations for FN in pediatric oncology patients. A retrospective chart review was utilized to evaluate newly diagnosed patients admitted for FN in the first 14 months of the pandemic compared with the same time period during the previous year. During the pandemic, the admission rate for FN was 28.9%, compared with 29.1% prepandemic ( P = 0.97). There was no significant difference in causative organisms when comparing time periods. In addition, the presence of a state government-enforced mask mandate was associated with an increased admission rate for FN during the pandemic period.